De novo mutation and skewed X‐inactivation in girl with BCAP31‐related syndrome. Issue 10 (22nd July 2020) - Kao, Hsiao‐Jung; Chiang, Hung‐Lun; Chen, Hsiao‐Huei; Fan, Pi‐Chuan; Tu, Yi‐Fang; Chou, Yen‐Yin; Hwu, Wuh‐Liang; Lin, Chien‐Ling; Kwok, Pui‐Yan; Lee, Ni‐Chung
Abstract: Full genome analysis of a young girl with deafness, dystonia, central hypomyelination, refractory seizure, and fluctuating liver function impairment revealed a heterozygous, de novo variant in the BCAP31 gene on chromosome Xq28 (NM_001256447.2:c.92G>A), mutations of which caused the X‐linked recessive severe neurologic disorder deafness, dystonia, and cerebral hypomyelination. Reverse transcription‐polymerase chain reaction of the patient's white blood cells showed the absence of wild‐type BCAP31 messenger RNA (mRNA) but the presence of two novel BCAP31 mRNAs. The major alternatively spliced mRNA is due to Exon 2 skipping and the utilization of a new initiation site in Exon 3 that leads to a frameshift and truncated transcript while the minor novel mRNA has a 110 nucleotide insertion to Exon 2. Phasing studies showed that the de novo variant arose in the paternal X chromosome. X chromosome inactivation assay was done and confirmed that the patient's maternal X chromosome was preferentially inactivated, providing evidence that the mutated BCAP31 gene was the one predominantly expressed. According to the American College of Medical Genetics and Genomics guideline, this variant is deemed "pathogenic" (PS2, PS3, PM2, PP3, and PP4) and deleterious. This is the first reported female patient in BCAP31 ‐related syndrome resulted from skewed X‐inactivation and a de novo mutation in the active X chromosome. Abstract : Full genome analysis of a young girl with deafness, dystonia, central hypomyelination, refractory seizure, and fluctuating liver function impairment revealed a heterozygous, de novo variant in the BCAP31 gene on chromosome Xq28 (NM_001256447.2:c.92G>A), mutations of which caused the X‐linked recessive severe neurologic disorder deafness, dystonia, and cerebral hypomyelination (MIM#300475). Reverse transcription‐polymerase chain reaction of the patient's white blood cells showed the absence of wild‐type BCAP31 messenger RNA (mRNA) but the presence of two novel BCAP31 mRNAs. The major alternatively spliced mRNA is due to Exon 2 skipping and the utilization of a new initiation site in Exon 3 that leads to a frameshift and truncated transcript while the minor novel mRNA has a 110 nucleotide insertion to Exon 2. Phasing studies showed that the de novo variant arose in the paternal X chromosome. X chromosome inactivation assay was done and confirmed that the patient's maternal X chromosome was preferentially inactivated, providing evidence that the mutated BCAP31 gene was the one predominantly expressed. This is the first reported female patient in BCAP31‐related syndrome resulted from skewed X‐inactivation and a de novo mutation in the active X chromosome.